ANALISIS HISTOLOGI TINGKAT KEMATANGAN GONAD IKAN KEMBUNG PEREMPUAN (Rastrelliger brachysoma, Bleeker 1851) DI PERAIRAN LEKOK, PASURUAN - Astuti, Septiana; Wiadnya, D.G.R; Sukandar, Mr (JFMR (Journal of Fisheries and Marine Research), 2019)
Rastrelliger brachysoma is an important economic fish for coastal communities. Rastrelliger brachysoma included in the red-list of species based on the IUCN of 2017 so the utilization of this species should be taken into account. Excessive and continuous utilization causes this species to dwindle. Fish catches of various sizes and unknown levels of gonad maturity of these fish resulted in female bloating becomes less and feared will be increasingly difficult to find in the water. Research on gonad girth level needs to be done to find out whether the fish catch is indeed feasible to be caught or not capture yet (in this case have experienced mature gonads). The results showed Rastrelliger brachysoma matured gonad on average length of 17.03 cm with sex ratio of 238 Â± 20,074 for female fish and the amount of 179 Â± 25,408 for male fish. Histologic analysis showed that Rastrelliger brachysoma was at maturity level of gonad I, II, III, IV and V while morphological analysis showed Rastrelliger brachysoma was in maturity level of gonad I, II, III and IV.